SISTEM INFORMASI MANAJEMEN PEMBELAJARAN PADA PEMBELAJARAN PRAKTIKUM LABORATORIUM DI JURUSAN PENDIDIKAN TEKNIK OTOMOTIF - Purwanto, Purwanto; sudarwanto, Sudarwanto; Sukaswanto, Sukaswanto (Jurnal Pendidikan Vokasi Otomotif, 2022)
The author reviews the importance of using management information systems in implementing and achieving efficient and effective learning. The role of technology is currently seen as helping systematic work. Technology can function to realize learning in a laboratory that is independent and better. Technology in the form of a learning management information system is expected to help students learn independently. The management information system is a means of monitoring laboratories' use, especially in the Department of Automotive Engineering Education. The conclusions obtained include: (1) the management information system is seen as helping educational institutions as a means of learning practicum in an independent laboratory, (2) supporting the management of laboratory facilities, (3) recording and distributing information appropriately, and (4) as a means of supporting operations another technical. In practice, SIM laboratory learning can be constrained by: (1) human resource competence and (2) an adequate level of technology. Finally, technological developments continue to pressure all parties to constantly adapt to overcome obstacles in the effective and efficient use of facilities, especially in the Ministry of Education Automotive Engineering.